Biometric multimodal security simulation on schedule Ii controlled drug - Hamdan, Muhammad Amree’ Ferdaus; Fuad, N.; Marwan, M.E (Scientific Academia Network (Scientiaca), 2020)
The paper present a multimodal (multi biometrics) security system focusing on the implementation of fingerprint recognition and facial feature recognition to enhance the existing method of security using password or personal identification number (PIN). This project is operated through a personal computer where all the identification for fingerprint and facial feature are done by using specific software. Successful identification will send a signal through a serial communication circuit and open an application. In this project, the final application should be a cupboard that store and secure schedule II controlled drug in hospital. Due to some problem, the final application was replaced by using a light emitting diode (LED) simulation circuit.